Formação de professores para o trabalho com a educação das relações étnico-raciais - Vanessa Regina Eleuterio Miranda (2018)
The objective of the research work was to analyze aspects of a curriculum of initial formation of pre-school teachers and in the initial years of elementary school, focusing on teacher training for the work of Ethnic-Racial Relations Education. It is a case study whose research was achieve in the Federal University of Minas Gerais (UFMG), an institution that stands out in the academic environment for the existence of several activities related to the racial issue, be it in the scope of militancy and political action of part of its academic community, or in the production and diffusion of knowledge on the subject, in its teaching, research and extension activities. The study focused on the curricula of the Pedagogy Course (face-to-face modality), with the aim of analyzing how to prepare teachers for work with the education of ethnic-racial relations, initial formation, as well as interests and relationships of power involved in the decisions and institutional actions and of their teachers to materialize this course/formative aspect. Using as analysis methodologies Content Analysis and Critical Discourse Analysis (ACD), the analysis focused on the set of curricular documents relatedto the course in question and on the perceptions and senses attributed, by teachers and students of the course, to the training to work with Ethnic-Racial Relations Education and, consequently, the curriculum